SMART Integrated Leadership (SMILE) for Smart City - Kustanto , Prio; Rahman , Rakhmadi (Jurnal Kajian Ilmiah, 2020)
The concept of a smart city which is becoming a big issue in big cities around the world encourages the active role and participation of the community in city management using a citizen centric approach so that there is a more dynamic and close interaction between citizens and service providers. The aim of implementing a Smart City is to be able to form and implement a city that is safe, comfortable, controlled and facilitates access for its citizens and strengthens the competitiveness of the city in terms of economy, social and technology. Smart cities must have a strong governance-oriented approach that emphasizes the role of social capital and relationships in urban development. The Smart City concept is no longer limited to ICT diffusion, but looks at people and society's needs. To meet and exceed citizen expectations, city leaders must innovate in core service areas in the application of the Smart City concept. In order to create innovative, creative and resilient leaders, it is necessary to design a Smart Integrated Leadership (SMILE) to support the success of a Smart City. Keywords: Smart City, Smart Integrated Leadership Abstrak Konsep kota cerdas (Smart City) yang menjadi isubesar di kota-kota besar di seluruh dunia mendorong peran aktif dan partisipasi masyarakat dalam pengelolaan kota menggunakan endekatan citizen centric sehingga terjadi interaksi yang lebih dinamis dan erat antara warga dengan penyedia layanan. Tujuan implementasi Smart City adalah untuk dapat membentuk dan menerapkan suatu kota yang aman, nyaman, terkendali dan mempermudah akses bagi warganya serta memperkuat daya saing kota dalam hal perekonomian, sosial dan teknologi. Smart city harus memiliki pendekatan pemerintahan yang berorientasi kuat yang menekankan peran modal sosial dan hubungan dalam pembangunan perkotaan. Konsep Smart City tidak lagi terbatas pada difusi TIK, tetapi melihat orang dan kebutuhan masyarakat. Untuk memenuhi dan melampaui harapan warga, pemimpin kota harus berinovasi di bidang layanan inti dalam penerapan konsep Smart City. Dalam rangka menciptakan para pemimpin inovatif, kreatif dan tangguh maka perlu dirancang Smart Integrated Leadership (SMILE) untuk mendukung suksesnya Smart City. Kata kunci: Smart City, Smart Integrated Leadership